New synthetic cannabinoids carrying a cyclobutyl methyl side chain: Human Phase I metabolism and data on human cannabinoid receptor 1 binding and activation of Cumyl‐CBMICA and Cumyl‐CBMINACA. Issue 8 (5th May 2021) - Haschimi, Belal; Grafinger, Katharina Elisabeth; Pulver, Benedikt; Psychou, Evangelia; Halter, Sebastian; Huppertz, Laura M.; Westphal, Folker; Pütz, Michael; Auwärter, Volker
Abstract: Synthetic cannabinoids (SCs) represent a large group of new psychoactive substances (NPS), sustaining a high prevalence on the drug market since their first detection in 2008. Cumyl‐CBMICA and Cumyl‐CBMINACA, the first representatives of a new subclass of SCs characterized by a cyclobutyl methyl (CBM) moiety, were identified in July 2019 and February 2020. This work aimed at evaluating basic pharmacological characteristics and human Phase I metabolism of these compounds. Human Phase I metabolites were tentatively identified by liquid chromatography–quadrupole time‐of‐flight mass spectrometry (LC‐QToF‐MS) of urine samples and confirmed by a pooled human liver microsome (pHLM) assay. The basic pharmacological evaluation was performed by applying a competitive ligand binding assay and a functional activation assay (GTPγS) using cell membranes carrying the human cannabinoid receptor 1 (hCB1 ). Investigation of the human Phase I metabolism resulted in the identification of specific urinary markers built by monohydroxylation or dihydroxylation. Although Cumyl‐CBMICA was primarily hydroxylated at the indole ring, hydroxylation of Cumyl‐CBMINACA mainly occurred at the CBM moiety. Both substances acted as agonists at the hCB1 receptor, although substantial differences could be observed. Cumyl‐CBMINACA showed higher binding affinity ( K i  = 1.32 vs. 29.3 nM), potency (EC50  = 55.4 vs. 497 nM), and efficacy ( E max  = 207% vs. 168%) than its indole counterpart Cumyl‐CBMICA. This study confirms that substitution of an indole by an indazole core tends to increase in vitro potency, which is potentially reflected by higher in vivo potency. The emergence and disappearance of SCs distributed via online shops carrying a CBM moiety once more demonstrate the "cat‐and‐mouse" game between manufacturers and legislation. Abstract : The present study aimed at evaluating the basic pharmacological characteristics and human Phase I metabolism of the two cyclobutyl methyl‐derived synthetic cannabinoids Cumyl‐CBMICA and Cumyl‐CBMINACA. Investigation of the biotransformation resulted in the identification of specific urinary markers built by monohydroxylation or dihydroxylation. Our data showed that substitution of an indole by an indazole core tends to increase in vitro potency, which is potentially reflected by higher in vivo potency.